Документи Центрального державного архіву Республіки Казахстан до біографії композитора Сергія Шабельського - Тлеубердіна, З. (Архіви України, 2008)
Based on the personal archives of Serhiy Shabel’s’kyi, a Ukrainian-born composer (1885-1956), the publication covers the description of his life and creative work, valuable contribution to the development of musical culture in Kazakhstan.